The pharmacodynamic profile of "Blackadder" blackcurrant juice effects upon the monoamine axis in humans: A randomised controlled trial. (2nd July 2020) - Watson, Anthony W.; Scheepens, Arjan; Kennedy, David O.; Cooney, Janine M.; Trower, Tania M.; Haskell-Ramsay, Crystal F.
Abstract : Emerging evidence from human intervention trials indicates health benefits of consuming blackcurrant fruit, including improvements to cognitive performance, modulation of blood flow, regulation of blood glucose and inhibition of enzymes underpinning normal cognitive function. Of particular relevance is our previous demonstration of monoamine oxidase (MAO)-A and B inhibition after the consumption of a New Zealand "Blackadder" blackcurrant juice in humans. The current study uses a double-blind, placebo-controlled, randomised cross- over design to assess the pharmacodynamics of the effects on platelet MAO-B inhibition and associated substrates, plasma prolactin levels and blood glucose levels after consumption of a single serve of "Blackadder" blackcurrant juice standardised to 500 mg polyphenols. Eight healthy male (20-–35 years) participants completed the trial. Measurements were obtained at baseline 15, 30, 45, 60, 100, 120, 150, 180, 240 mins and 24 h post dose. A fast, absolute and reversible inhibition of blood platelet MAO-B ( P  < 0.001) and a significant but delayed reduction in plasma prolactin ( P  < 0.001) were observed following the consumption of "Blackadder" blackcurrant juice when compared to a placebo control. No interpretable changes in substrates of MAO or associated metabolites were seen. These data provide a clear time course of the reversible inhibition of MAO-B after the single consumption of a of New Zealand "Blackadder" blackcurrant juice standardised at 500 mg of polyphenols and, therefore, provide a therapeutic window on which to base future nutritional interventions.